Penerapan Project Based Learning untuk Meningkatkan Keaktifan dan Mengurangi Kebosanan Siswa Kelas I Mi Ma’arif Nu Bebekan - Fitri Dwi Pertiwi; Moh. Agus Syairofi Syafii (TADHKIRAH: Jurnal Terapan Hukum Islam dan Kajian Filsafat Syariah, 2026)
This study aimed to increase students’ learning activeness and reduce boredom in Indonesian language lessons through the implementation of the Project Based Learning (PjBL) model for first-grade students at MI Ma’arif NU Bebekan. The research was conducted using an observation method during the learning process. The subjects of this study were first-grade students of MI Ma’arif NU Bebekan. Data were collected through observations of students’ activities, participation in learning, enthusiasm in completing projects, and responses during Indonesian language lessons. The observation results showed that the implementation of Project Based Learning had a positive impact on the learning process. Before the implementation of this model, some students appeared less active, easily bored, and less involved in classroom activities. After learning was carried out through project-based activities related to Indonesian language materials, students became more interested in participating in lessons, more confident in asking and answering questions, and more active in collaborating with their classmates to complete assignments. In addition, the learning atmosphere became more enjoyable because students were directly involved in activities connected to their daily experiences. Based on the findings, it can be concluded that the implementation of Project Based Learning was effective in increasing learning activeness and reducing boredom among first-grade students of MI Ma’arif NU Bebekan in Indonesian language lessons. This learning model can serve as an effective alternative for creating a more engaging, active, and meaningful learning experience for elementary school students.